High- and Low-Affinity Transport in Plants From a Thermodynamic Point of View - Dreyer, Ingo; Michard, Erwan (Frontiers in Plant Science, 2020)
Plants have to absorb essential nutrients from the soil and do this via specialized membrane proteins. Groundbreaking studies about half a century ago led to the identification of different nutrient uptake systems in plant roots. Historically, they have been characterized as ‘high-affinity’ uptake systems acting at low nutrient concentrations or as ‘low-affinity’ uptake systems acting at higher concentrations. Later this ‘high- and low-affinity’ concept was extended by ‘dual-affinity’ transporters. Here, in this study it is now demonstrated that the affinity concept based on enzyme kinetics does not have proper scientific grounds. Different computational cell biology scenarios show that affinity analyses, as they are often performed in wet-lab experiments, are not suited for reliably characterizing transporter proteins. The new insights provided here clearly indicate that the classification of transporters on the basis of enzyme kinetics is largely misleading, thermodynamically in no way justified and obsolete.